Autonomous motivation: school leaders as key drivers of physical activity in the Global Health Program - Guimaraes, R. F.; Bélisle, J.; Lamy, B.; Gaudet, R.; Doré, I.; Yao, P. L.; Barnett, T. A.; Carbonneau, N.; Girard, S. (Frontiers in Psychology, 2025)
IntroductionMotivation is one of the main factors that can influence physical activity practice in youth. Schools are ideal settings to provide opportunities to be active. However, few school-based behavioral change interventions have been designed with curriculum-based contents and evaluated in a real-life setting. The Global Health Program (GHP), implemented among 10,000 students in Québec (Canada), aims to promote long-term behavior change through educational strategies guided by school leaders. Therefore, the aim of the present study was to (i) investigate the association between school leaders’ implication and motivation for physical activity in GHP participants, and (ii) to test whether this association is moderated by physical activity level (active vs. inactive) or number of years of participation in the program.MethodsA cross-sectional study among children and adolescents participating in the GHP was conducted. The data collection was carried out in the Fall 2024 using self-report online questionnaires. Demographic data, motivation for physical activity, perception of school leaders’ implication and physical activity level were collected. Linear regressions analysis with interaction terms to examine potential moderating effect were used.ResultsResults showed that among the 658 participants (42% girls, mean ± SD age = 14.5 ± 1.8 years) 29.4% reported being active participants have been involved in GHP for an average of 3.1 ± 2.1 years. There was a positive association between school leaders’ implication and autonomous motivation [β̂ = 0.26; (95%CI 0.138; 0.256)]. However, neither PA level [β̂ = − 0.02, (95%CI −0.142; 0.104)] nor years of participation in GHP [β̂ = − 0.02, (95%CI −0.144; 0.102)] moderated this relationship.ConclusionResults support the importance of the role of school leaders on students’ motivational quality, regardless of their PA status or exposure length to intervention programs. This insight emphasizes the value of cultivating supportive school environments and leadership practices that consistently promote autonomous motivation, thereby encouraging long-term engagement in physical activity among youth, as fostered by the GHP in Québec (Canada).